Effect of Reduced Stiffness Dance Flooring on Lower Extremity Joint Angular Trajectories during a Ballet Jump. Issue 3 (September 2015) - Hackney, James; Brummel, Sara; Newman, Mary; Scott, Shannon; Reinagel, Matthew; Smith, Jennifer
We carried out a study to investigate how low stiffness flooring may help prevent overuse injuries of the lower extremity in dancers. It was hypothesized that performing a ballet jump (sauté) on a reduced stiffness dance floor would decrease maximum joint flexion angles and negative angular velocities at the hips, knees, or ankles compared to performing the same jump on a harder floor. The participants were 15 young adult female dancers (age range 18 to 28, mean = 20.89 ± 2.93 years) with at least 5 years of continuous ballet experience and without history of serious lower body injury, surgery, or recent pain. They performed sautés on a (low stiffness) Harlequin® WoodSpring Floor and on a vinyl-covered hardwood on concrete floor. Maximum joint flexion angles and negative velocities at bilateral hips, knees, and ankles were measured with the "Ariel Performance Analysis System" (APAS). Paired one-tailed t-tests yielded significant decreases in maximum knee angle (average decrease = 3.4° ± 4.2°, p = 0.026) and angular negative velocity of the ankles (average decrease = 18.7°/ sec ± 27.9°/sec, p = 0.009) with low stiffness flooring. If the knee angle is less acute, then the length of the external knee flexion moment arm will also be shorter and result in a smaller external knee flexion moment, given an equal landing force. Aso, high velocities of eccentric muscle contraction, which are necessary to control negative angular velocity of the ankle joint, are associated with higher risk of musculotendinous injury. Hence, our findings indicate that reduced floor stiffness may indeed help decrease the likelihood of lower extremity injuries.